Population and habitat use of Asian elephants (Elephas maximus) and five ungulate species in Khao Ang Rue Nai Wildlife Sanctuary, Chachoengsao Province, Thailand - KUSUMA MENKHAM; RONGLARP SUKMASUANG; MANANYA PLA-ARD; KHWANRUTAI CHARASPET; TARAPONE PANGANTA; YUNGYUT TRISURAT; NARIS BHUMPAKPHAN (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Menkham K, Sukmasuang R, Pla-Ard M, Charaspet K, Panganta T, Trisurat Y, Bhumpakphan N. 2019. Population and habitat use of Asian elephants (Elephas maximus) and five ungulate species in Khao Ang Rue Nai Wildlife Sanctuary, Chachoengsao Province, Thailand. Biodiversitas 20: 2213-2221. This study on the Asian elephant (Elephas maximus) population, habitat use and the diel activity patterns of elephants and five species of large even-toed ungulates was conducted between March 2017 and March 2018 in Khao Ang Rue Nai Wildlife Sanctuary, Chachoengsao Province using intensive camera trapping. Fifty-eight camera traps were deployed, adding up to a total of 4,463 trap nights and revealing 1,760 independent encounters. Six species of mammals were recorded, including the Asian elephant (Elephas maximus) and five species of large even-toed ungulates; the gaur (Bos gaurus), the banteng (Bos javanicus), the sambar deer (Rusa unicolor), the wild boar (Sus scrofa), and the muntjac (Muntiacus muntjak). The abundance analysis reflected that the probability occupancy of the elephant was 0.92 (SE = 0.04); in dry seasons 0.97 (SE = 0.04) and in wet seasons 0.90 (SE = 0.83). The population of elephants within the study site of 87.95 km2 was within 79.51-334.15 individuals. The elephant age classes were identified as adult, sub-adult, juvenile, and calf with percentages of 77.85%, 5.71%, 9.28%, and 7.14%, respectively. The adult male to adult female sex-ratio was 1: 1.39 and the adult female per calf ratio was 1: 0.12. The percentage of the calf to adult female ratio was 9.17%. Maximum Entropy analysis revealed that saltlicks and artificial water sources were the environmental factors that had the most influence on the probability of occurrence of the elephant (all year). We found that the diel activity pattern of the elephants was strongly nocturnal (85% recorded between 18.00-05.59 hours). Temporal overlapping was seen between elephants and gaurs, bantengs and sambar deer in order. Suggestions for area management include improvement of water sources, salt licks, grassland management, and providing education, publicization, and strict control to decrease human activities within the protected area. There also should be continuous studies to monitor the population and the ecology of these species.